1999
DOI: 10.1080/09629359990513
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Ferulic Acid and Isoferulic Acid on the Production of Macrophage Inflammatory Protein‐2 in Response to Respiratory Syncytial Virus Infection in RAW264.7 Cells

Abstract: WE in ves tigate d th e effect of ferulic acid (FA) and is oferulic acid (IFA),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(75 citation statements)
references
References 14 publications
4
70
0
1
Order By: Relevance
“…The progressive increase of MCP-1, MIP-1␤, and MIP-2 gene expressions at early time points in PBS control mice is consistent with previous reports of chemokine responses in RSV-infected human and murine cells in vitro (5,17,22,33). It also concurs with a mainly T-cell recruitment to the lungs during primary RSV infection (23,39).…”
Section: Discussionsupporting
confidence: 79%
“…The progressive increase of MCP-1, MIP-1␤, and MIP-2 gene expressions at early time points in PBS control mice is consistent with previous reports of chemokine responses in RSV-infected human and murine cells in vitro (5,17,22,33). It also concurs with a mainly T-cell recruitment to the lungs during primary RSV infection (23,39).…”
Section: Discussionsupporting
confidence: 79%
“…If so, then, what is the possible mechanism for the selective inhibition of TNF-α-induced expression of VCAM-1 in HUVEC by genipin? Given PPAR-γ activators can decrease expression of adhesion molecules in activated human endothelial cells [6,14,15] and PPAR-γ is expressed in vascular cells [16], we asked whether genipin induces PPAR-γ in HUVEC. We found that genipin up-regulated PPAR-γ expression in HUVEC by a concentration-and time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Ferulic acid has been shown to be among the main phenolic acids in C. heracleifolia (60) . Sakai et al (61) showed that ferulic acid and isoferulic acid could reduce macrophage inflammatory protein-2 production in a dose-dependent manner in RAW264 . 7 cells.…”
Section: Potential Health Benefits Of Phenolic Component Of Brewers' mentioning
confidence: 99%
“…7 cells. It was suggested that ferulic acid and isoferulic acid are responsible, at least in part, for the anti-inflammatory properties of the C. heracleifolia drug (61) . Recently published data have shown that ferulic acid and p-coumaric acid inhibited lipopolysaccharide-induced NO production and inducible NO synthase in macrophages (62) .…”
Section: Potential Health Benefits Of Phenolic Component Of Brewers' mentioning
confidence: 99%